REFUSAL STRATEGIES IN ENGLISH AND RUSSIAN - Paraskevi-Lukeriya L Iliadi; Tatiana V Larina (RUDN Journal of Language Studies, Semiotics and Semantics, 2017)
He article explores the speech act of refusal in British English and Russian and investigates British and Russian refusal strategies from the perspective of cross-cultural communication. The study aims to find similarities and differences between the ways of refusing requests, offers and invitations in different social contexts in two languages and cultures. It was conducted with the implementation of Speech Act Theo-ry (Austin 1962, Searle 1969, Searle & Vandervken 1985), Politeness Theory (Brown and Levinson 1987, Leech 1983, 2014, Larina and Leech 2014, Watts 2003), and the Theory of Cultural Scripts (Wierzbicka 1991/2003). The modified version of the Discourse Completion Test (DCT) developed by Beebe et al. (1990) was used for data collection. The study has revealed both quantitative and qualitative differences in refusal strategies which exist due to cultural differences, culture-specific politeness strategies and Communicative Styles (Larina 2015, Larina, Mustajoki, Protassova 2017). It has found that the Russians use more direct strategies than the British and are more taciturn and laconic. The British do more face-work to mitigate their refusal, they use both negative and positive strategies with higher regularity and are more voluble. The knowledge of communicative differences in refusal as well as in other speech acts is necessary for the acquisition and development of pragmatic competence of L2 English learners and successful intercul-tural communication.